How hydrology and landscape shape Odonata assemblages in marshlands crossed by ditches. (13th April 2022) - Crabot, Julie; Mauchamp, André; Bergerot, Benjamin; Bonis, Anne; Gore, Olivier; Rossignol, Nicolas; Paillisson, Jean‐Marc
Abstract: One of the major current ecological challenges is to understand how to reconcile human activities with biodiversity conservation concerns. This issue is particularly relevant in freshwater ecosystems where biodiversity is globally under severe threat. Artificial waterbodies, such as ditch networks, are part of the few remaining wetlands in agricultural landscapes and hence play a crucial role in maintaining aquatic biodiversity in these landscapes. We investigated the responses of adult Odonata assemblages at different spatial scales in a marshland crossed by ditches to two factors expected to be pivotal influences on assemblages. At the local scale, this was mainly the water regime in ditches and, at a broader scale, the composition of the landscape. Both taxonomic alpha and beta diversity, and functional trait composition were considered as response variables. Significant differences were found between the responses of the two Odonata suborders. We showed that Zygoptera species richness decreased and species turnover increased with the duration of drying episodes in ditches. Geographical distances between local assemblages as well as landscape characteristics, notably woodland cover, meadow cover and ditch network length, also significantly shaped the distribution of Zygoptera. For Anisoptera, species richness was not explained by environmental variables and beta diversity was associated only with local conditions; it increased with increasing dissimilarity in water quality and riparian vegetation. We also found evidence of functional trait syndromes (combinations of correlated traits) in Odonata assemblages, but without clear relationships to environmental gradients. This study reveals the structuring role of water regime for Odonata in ditch networks and demonstrates the need to jointly consider environmental variables at different spatial scales to properly understand the distribution of Odonata. Our findings have important conservation implications as the water regime is heavily managed in such ecosystems. Even though the relationship between functional composition and environmental gradients was found to be of limited extent in this study, we discuss how it might provide new insights for Odonata assemblage structure and be useful, locally, for stakeholders and managers. Lastly, we call for further multiscale investigations considering both the taxonomic and functional responses of Odonata assemblages (functional analyses with multiple traits and several species being scarce in this taxonomic group) in other anthropogenic freshwater ecosystems to gather more lessons for their conservation.